Transactions and Serverless are Made for Each Other. - Li, Qian; Kraft, Peter (Communications of the ACM, 2024)
Serverless cloud platforms, such as AWS Lambda and Azure Functions, are widely used for stateless applications due to their simplicity and scalability. This article explores how extending serverless platforms to support database transactions could unlock their potential for stateful, database-backed applications, including e-commerce and banking systems. By wrapping functions in transactions, these platforms can enable features like time-travel debugging and reliable execution with "exactly-once" semantics, addressing common challenges in distributed systems. Such advancements could significantly enhance debugging, reliability, observability, and performance for modern enterprise applications.